Characterization of Staphylococcus intermedius Group Isolates Associated with Animals from Antarctica and Emended Description of Staphylococcus delphini - Vrbovská, Veronika (Microorganisms, 2020)
Members of the genus Staphylococcus are widespread in nature and occupy a variety of niches, however, staphylococcal colonization of animals in the Antarctic environment has not been adequately studied. Here, we describe the first isolation and characterization of two Staphylococcus intermedius group (SIG) members, Staphylococcus delphini and Staphylococcus pseudintermedius, in Antarctic wildlife. Staphylococcus delphini were found exclusively in Adélie penguins. The report of S. pseudintermedius from Weddell seals confirmed its occurrence in all families of the suborder Caniformia. Partial RNA polymerase beta-subunit (rpoB) gene sequencing, repetitive PCR fingerprinting with the (GTG)(5) primer, and matrix-assisted laser-desorption/ionization time-of-flight mass spectrometry gave consistent identification results and proved to be suitable for identifying SIG members. Comparative genomics of S. delphini isolates revealed variable genomic elements, including new prophages, a novel phage-inducible chromosomal island, and numerous putative virulence factors. Surface and extracellular protein distribution were compared between genomes and showed strain-specific profiles. The pathogenic potential of S. delphini was enhanced by a novel type of exfoliative toxin, trypsin-like serine protease cluster, and enterotoxin C. Detailed analysis of phenotypic characteristics performed on six Antarctic isolates of S. delphini and eight reference strains from different animal sources enabled us to emend the species description of S. delphini.